2019
DOI: 10.3393/ac.2019.11.13
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Role of Carcinoembryonic Antigen in Clinical Practice

Abstract: Carcinoembryonic antigen (CEA) is not normally produced in significant quantities after birth but is elevated in colorectal cancer. The aim of this review was to define the current role of CEA and how best to investigate patients with elevated CEA levels. A systematic review of CEA was performed, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies were identified from PubMed, Cochrane library, and controlled trials registers. We identified 2,712 papers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 67 publications
(72 reference statements)
0
89
1
1
Order By: Relevance
“…Therefore, genetic-based studies are crucial in identifying biomarkers related to geographical, economic and pathological factors in a given population with a variety of ethnic features. CEA a fetal glycoprotein that is considered to be a tumor marker that is widely used to clinically evaluate the responses of patients to treatment and tumor prognosis (20). The normal level of CEA is <2.5 ng/ml in adult non-smokers and ≤5 ng/ml in adult smokers (20).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, genetic-based studies are crucial in identifying biomarkers related to geographical, economic and pathological factors in a given population with a variety of ethnic features. CEA a fetal glycoprotein that is considered to be a tumor marker that is widely used to clinically evaluate the responses of patients to treatment and tumor prognosis (20). The normal level of CEA is <2.5 ng/ml in adult non-smokers and ≤5 ng/ml in adult smokers (20).…”
Section: Discussionmentioning
confidence: 99%
“…CEA a fetal glycoprotein that is considered to be a tumor marker that is widely used to clinically evaluate the responses of patients to treatment and tumor prognosis (20). The normal level of CEA is <2.5 ng/ml in adult non-smokers and ≤5 ng/ml in adult smokers (20). Previous empirical studies and meta-analyses have found that measuring CEA levels can aid in monitoring chemotherapeutic responses in patients with CRC, particularly when imaging protocols are unsuitable for assessing these responses in clinical practice (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations